2021
DOI: 10.1177/17407745211056875
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying selection bias in cluster randomized trials

Abstract: Background In cluster randomized trials, patients are typically recruited after clusters are randomized, and the recruiters and patients may not be blinded to the assignment. This often leads to differential recruitment and consequently systematic differences in baseline characteristics of the recruited patients between intervention and control arms, inducing post-randomization selection bias. We aim to rigorously define causal estimands in the presence of selection bias. We elucidate the conditions under whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Fourth, we have primarily focused on the role of covariate adjustment for reducing chance imbalance and improving precision in CRTs and have not considered the use of covariates to address post-randomization selection nor recruitment bias, which involve yet another prevailing complexity in CRTs. Previous studies suggest that covariate adjustment helps reduce selection bias to a certain extent (Leyrat et al, 2013(Leyrat et al, , 2014 but is not a definitive solution especially in the presence of unmeasured variables predictive of recruitment (Li et al, 2021). The baseline imbalance we observed in our application to RESTORE trial (Table 3), therefore, might also be due to selection bias if the identification or recruitment of subjects was unblinded.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Fourth, we have primarily focused on the role of covariate adjustment for reducing chance imbalance and improving precision in CRTs and have not considered the use of covariates to address post-randomization selection nor recruitment bias, which involve yet another prevailing complexity in CRTs. Previous studies suggest that covariate adjustment helps reduce selection bias to a certain extent (Leyrat et al, 2013(Leyrat et al, , 2014 but is not a definitive solution especially in the presence of unmeasured variables predictive of recruitment (Li et al, 2021). The baseline imbalance we observed in our application to RESTORE trial (Table 3), therefore, might also be due to selection bias if the identification or recruitment of subjects was unblinded.…”
Section: Discussionmentioning
confidence: 80%
“…With regulators such as the U.S. Food and Drug Administration and the European Medicines Agency recommending prognostic baseline covariate adjustment in individually-randomized trials, there remains sufficient interest in fully understanding whether covariate adjustment can improve efficiency and precision in CRTs, especially when the number of clusters is often limited. Third, covariate adjustment may reduce selection or recruitment bias compared to the unadjusted analysis in CRTs (Leyrat et al, 2013(Leyrat et al, , 2014Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ignoring clustering and nesting during analyses can lead to an inflated type I error rate 3,[69][70][71][72] . There are additional issues, such as census recruitment or enrolling via cluster random sampling, a twostage process in which the population is divided into clusters and a subset of the clusters is randomly selected, as opposed to investigator led selection of clusters, which can be argued to induce bias and we refer the reader elsewhere for detailed discussions [73][74][75] .…”
Section: Cluster-randomized Controlled Trialsmentioning
confidence: 99%
“…Likewise, using real data from a CRT, Balzer et al recently showed the adjusted analysis was five times more efficient than an unadjusted analysis for the same parameter 16 . While our focus is on the potential of covariate adjustment to improve precision, we note that in other settings covariate adjustment may be essential to reducing bias due to missingness, selection, or restricted randomization 16‐25 …”
Section: Introductionmentioning
confidence: 92%
“…The Nj$$ {N}_j $$ study participants could be randomly sampled within a cluster or be a census of all persons in a cluster. Discussion of more complex settings with systematic sampling or other forces of selection bias is important but beyond the scope of this paper 16,20‐23 . Here, the study participants are representative of or comprise the cluster.…”
Section: Defining Causal Effects In Crtsmentioning
confidence: 99%